Prevalence of depression and anxiety and their predictors among patients undergoing maintenance hemodialysis in Northern China: a cross-sectional study. Issue 1 (31st December 2022) - Meng, Yan; Wu, Hao-tian; Niu, Jia-le; Zhang, Yuan; Qin, Hua; Huang, Liang-liang; Zhang, Xiao-jun; Yu, Lei; Yu, Hong-yan; Yan, Tao; Zhao, Jian-rong
Abstract: Objective: To investigate the prevalence of depression and anxiety in patients undergoing maintenance hemodialysis (MHD) in Hohhot, a large city on the northern border of China, and to identify independent risk factors for depression and anxiety in these patients. Methods: Patients receiving MHD for >3 months were enrolled in the four largest hemodialysis centers between September 2020 and December 2020. Depression and anxiety were assessed using the Zung self-rated depression scale (SDS) and Zung self-rated anxiety scale (SAS), respectively, with demographic and other data collected for logistic regression analyses. Results: Among 305 MHD patients included in this study, the prevalence of depression was 55.1%, including 27.5%, 21.0%, and 6.6% with mild, moderate and severe cases, respectively. The prevalence of anxiety was 25.9%, with 20.0%, 4.6%, and 1.3% having mild, moderate, and severe cases, respectively. An independent protective factor for depression was family income of ≥1415 US dollars/month relative to <157 US dollars/month (odds ratio [OR] 0.209, 95% confidence interval [CI] 0.065–0.673), and predictors of depression included ≥3 comorbidities (OR 18.527, 95% CI 1.674–205.028) and severe pruritus (OR 15.971, 95% CI 5.173–49.315). Independent predictors of anxiety included infrequent exercise (OR 3.289, 95% CI 1.411–7.664) and severe pruritus (OR 5.912, 95% CI 1.733–20.168). The correlation between depression and anxiety in these patients was significant ( rs  = 0.775, p  < 0.001). Conclusion: MHD patients in Northern China had high prevalence rates of depression (55.1%) and anxiety (25.9%). Lower family income, more comorbidities, and a higher degree of pruritus were predictors of depression, while infrequent exercise and severe pruritus were predictors of anxiety. Depression correlated significantly with anxiety. Attention should be given to family income, comorbidity, exercise, and pruritus severity for improved management of depression and anxiety among MHD patients.